VO2 kinetics and the O2 deficit in heavy exercise - Bearden, S. E.; Moffatt, R. J. (Journal of Applied Physiology, 2000)
The purpose of this study was to examine a new method for calculating the O2 deficit that considered the O2 uptake (O2) kinetics during exercise as two separate phases in light of previous research in which it was shown that the traditional O2 deficit calculation overestimated the recovery O2 consumption (ROC). Eight subjects completed exercise transitions between unloaded cycling and 25% (heavy, H) or 50% (very heavy, VH) of the difference between the lactic acid threshold (LAT) and peak O2 for 8 min. The O2 deficit, calculated in the traditional manner, was significantly greater than the measured ROC for both above-LAT exercises: 4.03 ± 1.01 vs. 2.63 ± 0.80 (SD) liters for VH and 2.36 ± 0.91 vs. 1.74 ± 0.63 liters for H for the O2 deficit vs. ROC (P < 0.05). When the kinetics were viewed as two separate components with independent onsets, the calculated O2 deficit (2.89 ± 0.79 and 1.71 ± 0.70 liters for VH and H, respectively) was not different from the measured ROC (P < 0.05). Subjects also performed the same work rate for only 3 min. These data, from bouts terminated before the slow component could contribute appreciably to the overall O2 response, show that the O2 requirement during the transition is less than the final steady state for the work rate, as evidenced by symmetry between the O2 deficit and ROC. This new method of calculating the O2 deficit more closely reflects the expected O2 deficit-ROC relationship (i.e., ROC O2 deficit). Therefore, estimation of the O2 deficit during heavy exercise transitions should consider the slow component of O2 as an additional deficit component with delayed onset.